Pre-teens, Audio Analgesia and Dental Care: A Cross-Sectional Study - Akshaye Kumar; Priyanka Sharma; Arjun Malhotra (International Healthcare Research Journal, 2020)
INTRODUCTION: Research has proven that music plays an important role in alleviating fear and anxiety among patients. AIM: To assess the effect of audio analgesia in pre-teen children aged 8-12 years undergoing dental restorations. MATERIALS AND METHOD: Data was collected using a pre-tested and pre-validated proforma filled by the child prior to start of the treatment by circling the number corresponding to the expected pain during the procedure [Ranged 0 (No pain) -10 (Maximum pain)]. Children who reported their expected pain above 5, were enrolled in group 1 (The ones receiving audio analgesia) while the remaining were assigned group 2 (controls). Children in group 1 were asked to put on their favourite song using noise cancellation headphones and the procedure was commenced. After completion of the treatment, the VAS scale was re-introduced and the children were asked to re-circle the actual pain experienced during the procedure. Data was analyzed using SPSS version 20.0 using the chi-squared test and Pearson’s correlation coefficient. A significant value was obtained when p was≤ 0.05. RESULTS: Of the total 80 children enrolled in the present study, there were an equal number of males and females (40 each). It was observed that 70.3% of children in group 1 had an increased pain tolerance as compared to only 37.2% of children in the control group(p=0.01). Pearson’s Correlation revealed a positive and linear association (r: +0.721) and a significant relationship (p = 0.03) between both groups. CONCLUSION: Audio analgesia has been proven to a promising alternative to distract the patient from the anxiety faced in the dental setting and is recommended for nervous and anxious patients.